2015
DOI: 10.1093/jb/mvv072
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of mutation-derived bias for alternate mating functionalities of theSaccharomyces cerevisiaeSte2p pheromone receptor

Abstract: Although well documented for mammalian G-proteincoupled receptors, alternate functionalities and associated alternate signalling remain to be unequivocally established for the Saccharomyces cerevisiae pheromone Ste2p receptor. Here, evidence supporting alternate functionalities for Ste2p is re-evaluated, extended and quantified. In particular, strong mating and constitutive signalling mutations, focusing on residues S254, P258 and S259 in TM6 of Ste2p, are stacked and investigated in terms of their effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Homodimerization is evolutionarily conserved. The yeast α‐factor receptor (Ste2p) shows a significant tendency to dimerize, and dimerization of functional receptors might be required for receptor signaling . Dimeric receptor complexes can even couple to a single G protein or arrestin molecule, as demonstrated for the light‐activated GPCR rhodopsin .…”
Section: Basal Receptor Localization and Agonist‐dependent Redistribumentioning
confidence: 99%
See 1 more Smart Citation
“…Homodimerization is evolutionarily conserved. The yeast α‐factor receptor (Ste2p) shows a significant tendency to dimerize, and dimerization of functional receptors might be required for receptor signaling . Dimeric receptor complexes can even couple to a single G protein or arrestin molecule, as demonstrated for the light‐activated GPCR rhodopsin .…”
Section: Basal Receptor Localization and Agonist‐dependent Redistribumentioning
confidence: 99%
“…The yeast α-factor receptor (Ste2p) shows a significant tendency to dimerize, 28,29 and dimerization of functional receptors might be required for receptor signaling. 30 Dimeric receptor complexes can even couple to a single G protein or arrestin molecule, as demonstrated for the light-activated GPCR rhodopsin. 31,32 Heteromers such as the μ-/κ-opioid receptor (μOR, κOR) dimer might couple to different effectors and induce functional effects distinct from their monomers.…”
Section: Receptor-receptor Interactionsmentioning
confidence: 99%
“…This phenomenon has been termed 'biased GPCR signaling' (reviewed extensively [9][10][11] ). While such research has largely been limited to mammalian systems, biased GPCR signaling has been observed in other phyla with the fungal pheromone receptor, Ste2p, in the model organism Saccharomyces cerevisiae serving as canonical example 12 .…”
mentioning
confidence: 99%
“…However, multiple studies have suggested the existence of alternate functionalities for S. cerevisiae Ste2p (ScSte2p), specifically in the mating events that occur downstream of cell cycle arrest, which are influenced by factors such as pheromone gradients [17][18][19][20] as well as localization of the ScSte2p receptor to the mating projection 21 . Furthermore, specific mutations in ligand-interacting residues of ScSte2p resulted in different effects on G-protein-mediated MAPK signaling and diploid zygote formation 12,22,23 . In contrast, much less is known about the counterparts of ScSte2p in multicellular fungi where the mating type of an organism is governed by more complex mechanisms, or where mating is not relevant to the fungal life cycle.…”
mentioning
confidence: 99%
“…Sc Ste2p has also been reported to exhibit alternate functionalities, dictated by factors such as pheromone gradients ( Segall, 1993 ; Brizzio et al., 1996 ; Elia, 1996 ; Barkai et al., 1998 ) and localization of the Sc Ste2p receptor to the mating projection ( Jackson et al., 1991 ). Mutations in the ligand-binding residues of the receptor alter G protein-mediated MAPK signaling and lead to different impacts on diploid zygote formation ( Dube and Konopka, 1998 ; Shi et al., 2007 ; Choudhary and Loewen, 2016a ).…”
Section: Introductionmentioning
confidence: 99%